The Importance of Private Enterprise and Small Businesses in Addressing the Employment Crisis - Bobojonov Hasan Karimovich (American Journal of Economics and Business Management, 2023)
Today, the socio-economic interests of small business entities, the problems arising in their economic activities, ensuring the stability of the "business cycle", interaction with other forms of economic management and the regulation of relations special attention is paid. Also, improving the economic mechanisms of small business management, ensuring socio-economic stability in the country by reducing the unemployment rate is one of the topical areas of the article.